Two new pyranoxanthones from Mesua beccariana - Soek, Sin Teh; Gwendoline, Cheng Lian Ee; Rahmani, Mawardi; Wei, Chung Sim; Siau, Hui Mah; Siow, Hwa Teo (MDPI, 2010)
Our recent study on the stem bark extracts of Mesua beccariana has led to the isolation of two new pyranoxanthones, mesuarianone (1) and mesuasinone (2), two anthraquinones, 4-methoxy-1,3,5-trihydroxyanthraquinone (3) and 2,5-dihydroxy-1,3,4-trimethoxyanthraquinone (4), one coumarin, mammea A/AB (5) and three common triterpenes, stigmasterol (6), friedelin (7) and betulinic acid (8). Structural elucidations of these compounds were achieved using 1D and 2D NMR and MS techniques. This is the first report on the phytochemistry of Mesua beccariana.